Pengaruh Polimer Kristal Cair (LCP) Terhadap Morfologi Campuran Pet/Pen - Wiwik Pudjiastuti (Balai Besar Kimia dan Kemasan, 1996)
The experiment of morfology and thermal properties of ternary polymer blends containing liquid crystalline polymer (vectra) has been done using differential scanning calorimeter, x ray measurement and scanning electron microscope.In the case of ternary blends, PET/PEN/LCP (vectra), LCP component were not miscible, with both PEN and PET ones and tended to form fibrous structures in the PET/PEN blend.